Implicit intertemporal trajectories in cognitive representations of the self and nation - Yamashiro JK; Liu JH; Zhang RJ (Springer Nature, 2023)
Individual selves and the collectives to which people belong can be mentally represented as following intertemporal trajectories—progress, decline, or stasis. These studies examined the relation between intertemporal trajectories for the self and nation in American and British samples collected at the beginning and end of major COVID-19 restrictions. Implicit temporal trajectories can be inferred from asymmetries in the cognitive availability of positive and negative events across different mentally represented temporal periods (e.g., memory for the past and the imagined future). At the beginning of COVID-19 restrictions, both personal and collective temporal thought demonstrated implicit temporal trajectories of decline, in which future thought was less positive than memory. The usually reliable positivity biases in personal temporal thought may be reversable by major public events. This implicit trajectory of decline attenuated in personal temporal thought after the lifting of COVID-19 restrictions. However, collective temporal thought demonstrated a pervasive negativity bias across temporal domains at both data collection points, with the collective future more strongly negative than collective memory. Explicit beliefs concerning collective progress, decline, and hope for the national future corresponded to asymmetries in the cognitive availability of positive and negative events within collective temporal thought.
Keywords: Autobiographical memory; Collective memory; Future thought; Intertemporal trajectories; Negativity bias; Humans; Mental Recall; COVID-19; Cognition